Accidental Injury in Children and its Clinical Pattern at Tertiary Neurological Center in Kathmandu - Gajuryal, Sharad Hari; Shrestha, Pranaya; Newal, Nicolla; Singh, Matrika; Shah, Manish Bikram; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
Introduction: Accidental injury in children is a significant cause of morbidity and mortality worldwide. The burden of child injuries in Nepal is not well understood due to lack of research into its epidemiology. This study aims to identity the prevalence of accidental injury as well as its clinical pattern in a tertiary Neurological Center in Nepal. Methods: A retrospective cross sectional study of pediatric patients presenting to Annapurna Neurological Institute with history of accidental injury between the period of 1 year. Data was collected using self-designed Performa which included socio-demographic profile, mode of injury, type of injury, place of injury and outcome. Results : Out of total 232 patients, 130 patients (56.03%) had history of Road Traffic Accident whereas 102 patients (43.97%) had history of fall injury. Head injury was the major cause of road traffic accident and fall. Majority of patients had accidental injury at home (41%), most of the injury occurs at morning. Mainly, injury occur by falling from window and terrace (49%) and majority of RTA occurred among pedestrians. Less than half patients are admitted to the ward and total of (6.4%) patient died after having accidental injuries during hospitalization. Conclusion: Pediatric accidental injury should be recognized as an important public health issue in Nepal. The high incidence of pediatric injury as a result of RTA and falls indicate the need for the identification of specific risk factors to reduce these injuries and implementation of stricter traffic rules and regulations and public education programs. A comprehensive injury registry in our set up seems to be important for formulating policies to reduce pediatric trauma burden.